Effect of weather variables on seasonal abundance of rice insects in southeast coastal region of Bangladesh - Md Niaz Morshed; Md Abdullah Al Mamun; Sheikh Arafat Islam Nihad; Md Mahfuzur Rahman; Naznin Sultana; Md Mezanur Rahman (Journal of Agriculture and Food Research, 2023)
The disclosure of insect incidence simultaneously with meteorological parameters is critical for developing management methods in the rice field. The number of hazardous and helpful insects, as well as meteorological conditions, were gathered on a daily basis for three years to determine when the insect population was at its peak. Throughout the rice seasons, rice yellow stem borer, caseworm, green leafhopper, field cricket, carabid beetle, and ladybird beetle were observed to be prominent. The Aman season (July–December) has the most insects, and the transition time between Boro (December–May) and Aus (April–August) has been identified as critical for the largest abundance of insect population. Maximum temperature is favorably and strongly associated to insect population abundance, but rainfall is adversely connected to insect population reduction. In the instance of the Aus season, the optimal maximum, minimum, and mean temperatures were 31°C–35°C, 20.43°C–28.32°C, and 25.35°C–32.15°C, respectively. Whereas for Aman, temperatures ranging from 30.76°C to 36.04°C, 20.42°C–28.40°C, and 25.81°C–31.55°C, respectively, and for Boro, temperatures ranging from 19.65°C to 35.7°C, 15.66°C–26.10°C, and 17.16°C–29.96°C, respectively, have been shown to be most conducive to insect abundance. In addition to the environmental criteria mentioned above, rainfall of less than 20 mm in Aus and Aman and less than10 mm in Boro season are beneficial for the maximum insect prevalence. The current study's findings will help researchers and farmers to make early warning decisions and to develop crop advisories based on meteorological parameters to manage insects in rice fields.